Notice of emergency meeting
038-0075-001 THIS IS TO INFORM YOU THAT THERE WILL BE AN EMERGENCY MEETING OF THE BASQUE CHILDREN'S COMMITTEE TOGETHER WITH THE NATIONAL JOINT COMMITTEE FOR SPANISH RELIEF AND THE BRITISH COMMITTEE FOR REFUGEES FROM SPAIN, at 30, ECCLESTON STREET, S.W.1. at 5.pm. ON TUESDAY SEPTEMBER 5th, 1939. IT IS VERY MUCH HOPED YOU WILL BE ABLE TO ATTEND. returning from Budleigh 292/946/38/75